Exploring the High of School Dropout Rate: a Case Study on Bajo Tribe in South Sulawesi Indonesia - Sudirman; Muliadi; Jauhar (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to find out the high incidence of school dropout in recent times. A study was conducted in Bajo tribe, South Sulawesi, Indonesia. The enrollment rate of children in primary school is lacking in this area. This research uses a qualitative case study approach in Bajo tribe to explore this phenomenon as clearly as possible. Observation, unstructured interviews with teachers, parent, and chieldren and a review of official documents were used for data collection. The data were analyzed descriptively and qualitatively. The results of this study, the high dropout rate for Bajo children were due to four main factors: for Bajo children: (1) cultural and environmental, (2) low family income, (3) school curriculum, classroom facilities, and teacher teaching methods, and (4) children's own life habits. In doing so, it is necessary to provide education services in a proportional way according to the characteristics and the natural of Bajo children. For futher research is needed to do something about how to minimize the number of Bajo children who dropout